PENGARUH FILTER BUBBLE DALAM MEDIA SOSIAL TERHADAP PERSEPSI MAHASISWA TENTANG CITRA KEPOLISIAN (Survei Pada Mahasiswa di Jakarta) - Dita Yunisa (2023)
This study aims to see whether the motives for using social media, awareness of the recommendation system, and preventive actions against filter bubbles affect students' perceptions of the image of the police. To answer this question, this study conducted a survey of 100 student participants in Jakarta using Eli Pariser's filter bubble theory. The method used is quantitative using primary data sources in the form of surveys of respondents and secondary data in the form of interviews and literature studies from scientific sources and previous studies. The results of the study show that these three variables influence the formation of perceptions about the image of the police by 61.8%. The trend in obtaining information has changed in recent times where people are more likely to seek information via social media because of the easy access and speed of information circulation, it needs to be followed by the awareness that recommendation systems on social media can direct users to information according to previously held values and limit it to different information and views.